THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY, AND PROMOTION ON THE PURCHASE DECISION OF INDOMILK PRODUCTS IN BATAM CITY - Angeline; Nora Pitri Nainggolan (International Journal Management and Economic, 2026)
This study aims to analyze the influence of brand image, product quality, and promotion on purchasing decisions for Indomilk products in Batam City. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to Indomilk consumers domiciled in Batam City with a total of 119 respondents. The sampling technique used purposive sampling with the criteria that respondents had purchased Indomilk products and were at least 17 years old. Data analysis was conducted using descriptive statistics and multiple linear regression with the help of SPSS version 26. The results showed that partially brand image, product quality, and promotion had a positive and significant effect on purchasing decisions for Indomilk products in Batam City. Simultaneously, the three independent variables also had a significant effect on purchasing decisions. These findings indicate that consumer purchasing decisions are not only influenced by one factor, but are a combination of positive brand perceptions, good product quality, and effective promotional strategies. Findings study This give implications strategic for company in formulate marketing strategies use increase decision purchase consumers.